Country Partnership Framework for Islamic Republic of Mauritania for the Period of FY18-FY23 - World Bank Group (World Bank, Washington, DC, 2018)
Mauritania’s abundant endowment of natural resources, its strategic location at the gateway between Sub‐Saharan and Northern Africa, its richly diverse, yet stratified, cultural and social make‐up and its position in a restive region, increasingly beholden to the ravaging effects of climate change, create a complex development space for poverty reduction and shared prosperity. The end of the commodity super‐cycle brought these challenges to the fore, marking a decisive turning point in Mauritania’s quest to end poverty and achieve shared prosperity by 2030. This Country Partnership Framework (CPF) for Mauritania lays out the program for the period of FY18–FY23 and reflects lessons from the Completion and Learning Review (CLR) of the preceding FY14‐FY16 Country Partnership Strategy (CPS), which was discussed at the Board in September 2013. The CPF will support the transition to a more inclusive, diversified and resilient model of growth, building on Mauritania’s natural resource wealth. First, it expands opportunities for economic diversification with interventions to raise productivity in traditional livestock, fisheries, and agricultural activities; improves household welfare through access to basic services; and enables increased participation in economic activity which will further sustain growth. Second, interventions in education, health and social protection will emphasize quality and access for the most vulnerable population segments and employability of youth and women. Third, it supports improvements in economic governance to optimize revenue mobilization and public spending, create opportunities for the private sector and strengthen the transparency of the extractives sector. The CPF emphasizes adaptation to the effects of climate change and building environmental resilience, as well as macroeconomic stability to ensure economic resilience. Finally, the CPF will feature a sharpened focus on private sector development, seeking to foster a more level playing field to accelerate the nascent transition from public to private sector‐led growth. This will be achieved through even closer collaboration between IDA, IFC and MIGA in maximizing finance for development.